2021
DOI: 10.1128/mbio.01707-21
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Outer Membrane Vesicles as a Versatile Tool in Vaccine Research and the Fight against Antimicrobial Resistance

Abstract: Gram-negative bacteria include a number of pathogens that cause disease in humans and animals. Although antibiotics are still effective in treating a considerable range of infections caused by Gram-negative bacteria, the alarming increase of antimicrobial resistance (AMR) induced by excessive use of antibiotics has raised global concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 115 publications
0
21
0
Order By: Relevance
“…5 is beyond the scope of the present study, previous reports have demonstrated clear effects of efficient vaccine programs in aquaculture as an example of the potential impact of just one of the factors in Fig. 5 ( 37 , 38 ). Vaccine use would therefore have been an ideal parameter to include in the current study, as it would be expected to have a substantial effect, and future research projects should include vaccine data collection from all or subsets of Danish aquaculture sites, considering vaccine coverage and route of administration (injection, immersion, etc.…”
Section: Discussionmentioning
confidence: 80%
“…5 is beyond the scope of the present study, previous reports have demonstrated clear effects of efficient vaccine programs in aquaculture as an example of the potential impact of just one of the factors in Fig. 5 ( 37 , 38 ). Vaccine use would therefore have been an ideal parameter to include in the current study, as it would be expected to have a substantial effect, and future research projects should include vaccine data collection from all or subsets of Danish aquaculture sites, considering vaccine coverage and route of administration (injection, immersion, etc.…”
Section: Discussionmentioning
confidence: 80%
“…However, the spontaneous release of OMVs is insufficient, resulting in low yields. 12 Thus, methods capable of increasing OMV production are needed for practical biological applications. Although the information about the molecular mechanisms of their dynamic production and shedding is limited, crosslinks bridging the outer membrane to PG, the lipid composition dictating membrane fluidity, and the accumulation of misfolded molecules may play essential roles in the biogenesis of OMVs.…”
Section: Biogenesis Of Omvsmentioning
confidence: 99%
“…They contain various types of cargo, such as genetic material (DNA or RNA) and toxins, which are involved in diverse bacterial and bacteria-host interactions (Kaparakis-Liaskos and Ferrero, 2015;. MVs have also been used as platforms for vaccine development and as drug delivery systems (Toyofuku et al, 2015;Zhu et al, 2021). Initial research on MVs in Gram-negative bacteria showed that they formed through the blebbing of the outer membrane (Chatterjee and Das, 1967;Devoe and Gilchrist, 1973).…”
Section: Signal Delivery Through Membrane Vesicles (Mvs)mentioning
confidence: 99%